A vertical anti-seepage material based on modified attapulgite and its preparation and application

Through the preparation of modified concave and convex rock mud, combined with microcrystalline cellulose and surfactant, an efficient vertical anti-seepage material was formed, which solved the problem of increased permeability of the Middle-bentonite isolation wall in the contaminated site, significantly improving the prevention The permeability and adsorption capacity extend the service life of the anti-seepage barrier.

CN117843282BActive Publication Date: 2024-12-13ANHUI URBAN CONSTR DESIGN & RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311849568.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2024-12-13
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

The existing soil-bentonite vertical isolation walls have increased permeability in contaminated sites, affecting the long-term service performance of anti-fouling barriers. The research on concave and concave rock stones as anti-seepage materials is still in the exploration stage, and the adsorption capacity and anti-seepage performance are insufficient. .

Method used

Using modified concave and convex rock mud, through the combination of microcrystalline cellulose, catalyst, carboxymethyl cellulose, cetyl trimethyl ammonium bromide and terminal amino polyamide amine, through hydrothermal treatment and calcination, Form activated concave and concave rock stone with high specific surface area and excellent mechanical properties, combining cetyl trimethylammonium bromide and end amino polyamide amine, enhance its adsorption properties, and mix it with the consolidation material to form a vertical anti-seepage material .

Benefits of technology

It significantly improves the salt and acid and alkali resistance of the anti-seepage wall, enhances the adsorption ability and crack resistance, optimizes the construction ease and anti-seepage and pollution resistance, and extends the service life of the anti-seepage barrier.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117843282B_ABST
    Figure CN117843282B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified attapulgite slurry for a vertical anti-seepage material for a contaminated site, and the raw materials thereof include: attapulgite, microcrystalline cellulose, a catalyst, a zinc chloride solution with a concentration of 0.1-1 mol / L, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, and amino-terminated polyamide amine; the mass ratio of attapulgite, microcrystalline cellulose, a catalyst, a zinc chloride solution, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, and amino-terminated polyamide amine is 10-30:1-5:0.1-1:50-150:1-2.5:1-3:1-3. The present invention discloses a method for preparing the modified attapulgite slurry for a vertical anti-seepage material for a contaminated site. The present invention also discloses a vertical anti-seepage material based on modified attapulgite, and the raw materials thereof include: the modified attapulgite slurry for a vertical anti-seepage material for a contaminated site and a consolidation material; the consolidation material is a hydraulic material or / and soil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental geotechnical engineering, and in particular to a modified attapulgite slurry used as a vertical anti-seepage material for polluted sites and a preparation method thereof, a vertical anti-seepage material based on modified attapulgite and the preparation and application thereof. Background Art

[0002] Soil-(cement)-bentonite vertical isolation walls are widely used in vertical anti-pollution barrier projects in contaminated sites due to their simple construction, low cost and low permeability.

[0003] However, the composition of leachate in contaminated sites is complex, which can significantly increase the permeability of soil-bentonite vertical isolation walls, thereby affecting the long-term service performance of the anti-pollution barrier. Therefore, the development of vertical isolation wall materials with strong chemical properties is one of the problems that need to be solved in the field of vertical anti-seepage technology for contaminated sites.

[0004] Attapulgite, also known as "palygorskite", is a hydrous magnesium-rich, aluminum silicate clay mineral with a layer-chain crystal structure and a unique fibrous structure. Attapulgite has a loose structure, well-developed pores, and a large specific surface area. The high-valent cations in its silicon-oxygen tetrahedron are easily replaced by low-valent cations, generating excess negative charges, making its surface charge unbalanced, and ultimately giving it a strong cation exchange capacity. It can be seen from this that attapulgite has high adsorption performance and is a good adsorption material, and has been fully developed and applied in this regard.

[0005] In addition, attapulgite also has similar properties to expansive soil, such as strong water absorption and plasticity. However, unlike expansive soil, although attapulgite expands rapidly after absorbing water, it has a low water loss rate under the same conditions, is not prone to cracks, and is not easily disturbed by changes in the external chemical environment. It is a highly potential anti-fouling barrier material.

[0006] At present, the application research of attapulgite ore at home and abroad is mainly concentrated in the fields of petrochemical industry, daily chemical industry, fine chemical industry, food processing, etc.

[0007] As people pay more attention to ecological environment protection, attapulgite has gradually been used in environmental geotechnical fields such as sewage treatment and soil pollution remediation in recent years due to its unique physical and chemical properties such as adsorption, colloid, reinforcement, and carrier. However, attapulgite has poor adsorption capacity and poor anti-seepage performance. Research on attapulgite as an anti-seepage material is still in the exploratory stage. Summary of the invention

[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a modified attapulgite slurry for vertical anti-seepage materials for contaminated sites and a preparation method thereof, a vertical anti-seepage material based on modified attapulgite and its preparation and application.

[0009] A modified attapulgite slurry for vertical anti-seepage materials in contaminated sites, the raw materials of which include: attapulgite, microcrystalline cellulose, a catalyst, a zinc chloride solution with a concentration of 0.1-1 mol / L, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, and amino-terminated polyamidoamine; the mass ratio of the attapulgite, microcrystalline cellulose, the catalyst, the zinc chloride solution, carboxymethyl cellulose, hexadecyltrimethylammonium bromide, and amino-terminated polyamidoamine is 10-30: 1-5: 0.1-1: 50-150: 1-2.5: 1-3: 1-3.

[0010] Preferably, the catalyst is ammonium ferrous sulfate hexahydrate.

[0011] The method for preparing the modified attapulgite slurry used as a vertical anti-seepage material for contaminated sites comprises the following steps:

[0012] S1, adding carboxymethyl cellulose to anhydrous ethanol and stirring evenly, and adding deionized water thereto to obtain prefabricated carboxymethyl cellulose;

[0013] S2, grinding and sieving the attapulgite, calcining at high temperature for 1-3 hours, the calcination temperature is 200-500° C., and then adding microcrystalline cellulose after cooling and grinding evenly to obtain a cellulose-attapulgite composite;

[0014] S3, adding the cellulose-attapulgite complex to water, adding a catalyst and stirring evenly, hydrothermally treating at 200-240° C. for 5-10 hours, taking out and placing in a zinc chloride solution for 1-10 hours, filtering, drying, keeping warm in a tubular furnace at 300-500° C. for 10-30 minutes, cooling to room temperature, washing to neutrality, drying, and crushing to obtain activated attapulgite;

[0015] S4. Add deionized water to the activated attapulgite and stir evenly, pour prefabricated carboxymethyl cellulose into it under stirring, add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine and stir.

[0016] Preferably, in S1, deionized water is added until the concentration of carboxymethyl cellulose in the system is 5-10 mmol / L.

[0017] Preferably, in S2, the grinding pressure is 1-2.5 MPa, and the grinding speed is 1000-5000 r / min.

[0018] Preferably, in S3, neutral hydrochloric acid with a concentration of 1-1.5 mol / L is used for washing.

[0019] Due to the strong electrostatic attraction and hydrogen bond interaction between naturally produced attapulgite crystals, they are prone to form agglomerates, making it difficult for its dispersion function to be effectively exerted.

[0020] The present invention prepares a composite of calcined attapulgite and microcrystalline cellulose, and grinds the microcrystalline cellulose to fully disperse it into the pore structure of the attapulgite, thereby achieving high bonding strength; and then hydrothermally treating the calcined attapulgite to deposit a nano carbon structure on its surface, and using zinc chloride for activation, so that the obtained activated attapulgite not only has a large specific surface area and excellent mechanical properties, but also has extremely high affinity with carboxymethyl cellulose and good dispersibility; and after being coordinated with hexadecyltrimethylammonium bromide, the attapulgite can react with amino-terminated polyamide amine, thereby achieving high bonding strength between the two.

[0021] Hexadecyltrimethylammonium bromide, as a cationic surfactant, is compounded with activated attapulgite and amino-terminated polyamide amine to give the product excellent adsorption properties; when used as a vertical barrier material for contaminated sites, it can effectively block the pollution of pollutants to the water and soil around the site.

[0022] A vertical anti-seepage material based on modified attapulgite, the raw materials of which include: the modified attapulgite slurry used for the vertical anti-seepage material of polluted sites and a consolidation material; the consolidation material is a hydraulic material and / or soil.

[0023] Preferably, the dry mass of the modified attapulgite slurry used as a vertical anti-seepage material for contaminated sites accounts for 25-35% of the dry mass of the system.

[0024] Preferably, the hydraulic material is at least one of ordinary Portland cement, slag Portland cement, alkali-activated blast furnace slag, fly ash, alkali slag, and carbide slag.

[0025] Preferably, the soil is at least one of on-site trench excavation waste soil, clay, and silt.

[0026] The method for preparing the vertical anti-seepage material based on modified attapulgite is to add a consolidation material to the modified attapulgite slurry used for the vertical anti-seepage material for contaminated sites and stir the mixture evenly.

[0027] The modified attapulgite-based vertical anti-seepage material is used as a vertical isolation wall material in contaminated sites.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] (1) Using modified attapulgite to replace bentonite in the mud wall can significantly improve the salt resistance, acid and alkali resistance and other properties of the anti-seepage wall while ensuring the anti-seepage performance of the wall, thus providing a guarantee for the long-term service performance of the anti-seepage barrier project.

[0030] (2) The modified attapulgite has better dispersibility than bentonite. After modification, the adsorption performance of attapulgite is further enhanced, which further enhances the blocking effect of pollutants in the leachate of the vertical anti-fouling barrier, and ultimately optimizes the construction and workability of the wall material and its anti-seepage and anti-fouling performance.

[0031] (3) Attapulgite clay is cheap and has low use cost; the modified reagents used are environmentally friendly materials that will not cause pollution and have obvious advantages in the prevention and control of polluted sites.

[0032] (4) After the modified attapulgite slurry is consolidated with the hydraulic material / soil, it can effectively enhance the anti-cracking strength of the system, which not only greatly enhances the bearing capacity of the vertical anti-seepage material, but also achieves the goal of anti-seepage and anti-fouling performance after the wall is formed. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a comparison chart of the unconfined compressive strength and permeability coefficient of the samples made of the vertical anti-seepage materials obtained by Example 5 and Comparative Examples 1-2 after 28 days of curing.

[0034] Figure 2 The figure is a comparison chart of the adsorption retardation rates of different pollutants of the samples made of the vertical anti-seepage materials obtained by Example 5 and Comparative Examples 1-2 after 28 days of curing. DETAILED DESCRIPTION

[0035] The present invention will be further explained below in conjunction with specific embodiments.

[0036] Example 1

[0037] A modified attapulgite slurry for vertical anti-seepage materials in contaminated sites, the raw materials of which include: 10kg of attapulgite, 1kg of microcrystalline cellulose, 0.1kg of ammonium ferrous sulfate hexahydrate, 50kg of 0.1mol / L zinc chloride solution, 1kg of carboxymethyl cellulose, 1kg of hexadecyltrimethylammonium bromide, and 1kg of amino-terminated polyamidoamine.

[0038] The above-mentioned modified attapulgite slurry preparation method comprises the following steps:

[0039] S1, adding carboxymethyl cellulose to 10 kg of anhydrous ethanol and stirring evenly, adding deionized water thereto until the concentration of the carboxymethyl cellulose is 5 mmol / L, to obtain prefabricated carboxymethyl cellulose;

[0040] S2, grinding the attapulgite through a 200 mesh sieve, calcining at high temperature for 1 hour, the calcination temperature is 200° C., and then adding microcrystalline cellulose to grind evenly after cooling, the grinding pressure is 1 MPa, and the grinding speed is 1000 r / min to obtain a cellulose-attapulgite composite;

[0041] S3, adding the cellulose-attapulgite composite to 20 kg of water, adding ammonium ferrous sulfate hexahydrate and stirring evenly, hydrothermally treating at a temperature of 200° C. for 5 h, adding to a zinc chloride solution and standing for 1 h, filtering, drying, keeping warm in a tubular furnace at a temperature of 300° C. for 10 min, cooling to room temperature, washing with 1 mol / L hydrochloric acid to neutralize, drying, and crushing to obtain activated attapulgite;

[0042] S4. Add 20 kg of deionized water to the activated attapulgite and stir evenly. Pour the prefabricated carboxymethyl cellulose into the mixture while stirring. Stir at 400 r / min for 15 min. Add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine. Stir at 400 r / min for 2 h.

[0043] A method for preparing a vertical anti-seepage material based on modified attapulgite is provided. Uncontaminated in-situ soil is added to the modified attapulgite slurry obtained in this embodiment and stirred evenly, and the dry mass of the modified attapulgite slurry accounts for 25% of the dry mass of the system.

[0044] Example 2

[0045] A modified attapulgite slurry for vertical anti-seepage materials in contaminated sites, the raw materials of which include: 30kg of attapulgite, 5kg of microcrystalline cellulose, 1kg of ammonium ferrous sulfate hexahydrate, 150kg of 1mol / L zinc chloride solution, 2.5kg of carboxymethyl cellulose, 3kg of hexadecyltrimethylammonium bromide, and 3kg of amino-terminated polyamidoamine.

[0046] The above-mentioned modified attapulgite slurry preparation method comprises the following steps:

[0047] S1, adding carboxymethyl cellulose to 30 kg of anhydrous ethanol and stirring evenly, adding deionized water thereto until the concentration of the carboxymethyl cellulose is 10 mmol / L, to obtain prefabricated carboxymethyl cellulose;

[0048] S2, grinding the attapulgite through a 200 mesh sieve, calcining at high temperature for 3 hours, the calcination temperature is 500° C., and then adding microcrystalline cellulose to grind evenly after cooling, the grinding pressure is 2.5 MPa, and the grinding speed is 5000 r / min to obtain a cellulose-attapulgite composite;

[0049] S3, adding the cellulose-attapulgite composite to 40 kg of water, adding ammonium ferrous sulfate hexahydrate and stirring evenly, hydrothermally treating at a temperature of 240° C. for 10 hours, adding to a zinc chloride solution and standing for 10 hours, filtering, drying, keeping warm in a tubular furnace at a temperature of 500° C. for 30 minutes, cooling to room temperature, washing with 1.5 mol / L hydrochloric acid to neutralize, drying, and crushing to obtain activated attapulgite;

[0050] S4. Add 60 kg of deionized water to the activated attapulgite and stir evenly. Pour the prefabricated carboxymethyl cellulose into the mixture while stirring. Stir at a speed of 800 r / min for 25 min. Add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine. Stir at a speed of 800 r / min for 4 h.

[0051] A method for preparing a vertical anti-seepage material based on modified attapulgite is provided. Fly ash is added to the modified attapulgite slurry obtained in this embodiment and stirred evenly, and the dry mass of the modified attapulgite slurry accounts for 35% of the dry mass of the system.

[0052] Example 3

[0053] A modified attapulgite slurry for vertical anti-seepage materials in contaminated sites, the raw materials of which include: 15 kg of attapulgite, 4 kg of microcrystalline cellulose, 0.3 kg of ammonium ferrous sulfate hexahydrate, 80 kg of 0.8 mol / L zinc chloride solution, 2 kg of carboxymethyl cellulose, 1.5 kg of hexadecyltrimethylammonium bromide, and 2.5 kg of amino-terminated polyamidoamine.

[0054] The above-mentioned modified attapulgite slurry preparation method comprises the following steps:

[0055] S1, adding carboxymethyl cellulose to 15 kg of anhydrous ethanol and stirring evenly, adding deionized water thereto until the concentration of the carboxymethyl cellulose is 9 mmol / L, to obtain prefabricated carboxymethyl cellulose;

[0056] S2, grinding the attapulgite through a 200 mesh sieve, calcining at high temperature for 1.5 h, the calcination temperature is 400° C., and then adding microcrystalline cellulose to grind evenly after cooling, the grinding pressure is 1.5 MPa, and the grinding speed is 4000 r / min to obtain a cellulose-attapulgite composite;

[0057] S3, adding the cellulose-attapulgite composite to 25 kg of water, adding ammonium ferrous sulfate hexahydrate and stirring evenly, hydrothermally treating at a temperature of 230° C. for 7 hours, adding to a zinc chloride solution and standing for 8 hours, filtering, drying, keeping warm in a tubular furnace at a temperature of 350° C. for 25 minutes, cooling to room temperature, washing with 1.1 mol / L hydrochloric acid to neutralize, drying, and crushing to obtain activated attapulgite;

[0058] S4. Add 50 kg of deionized water to the activated attapulgite and stir evenly. Pour the prefabricated carboxymethyl cellulose into the mixture while stirring. Stir at a speed of 500 r / min for 22 min. Add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine. Stir at a speed of 500 r / min for 3.5 h.

[0059] A method for preparing a vertical anti-seepage material based on modified attapulgite, wherein clay is added to the modified attapulgite slurry obtained in this embodiment and stirred evenly, and the dry mass of the modified attapulgite slurry accounts for 27% of the dry mass of the system.

[0060] Example 4

[0061] A modified attapulgite slurry for vertical anti-seepage materials in contaminated sites, the raw materials of which include: 25 kg of attapulgite, 2 kg of microcrystalline cellulose, 0.7 kg of ammonium ferrous sulfate hexahydrate, 120 kg of 0.2 mol / L zinc chloride solution, 1.5 kg of carboxymethyl cellulose, 2.5 kg of hexadecyltrimethylammonium bromide, and 1.5 kg of amino-terminated polyamidoamine.

[0062] The above-mentioned modified attapulgite slurry preparation method comprises the following steps:

[0063] S1, adding carboxymethyl cellulose to 25 kg of anhydrous ethanol and stirring evenly, adding deionized water thereto until the concentration of the carboxymethyl cellulose is 7 mmol / L, to obtain prefabricated carboxymethyl cellulose;

[0064] S2, grinding the attapulgite through a 200 mesh sieve, calcining at high temperature for 2.5 hours, the calcination temperature is 300° C., and then adding microcrystalline cellulose to grind evenly after cooling, the grinding pressure is 2 MPa, and the grinding speed is 2000 r / min to obtain a cellulose-attapulgite composite;

[0065] S3, adding the cellulose-attapulgite composite to 35 kg of water, adding ammonium ferrous sulfate hexahydrate and stirring evenly, hydrothermally treating at a temperature of 210° C. for 9 hours, adding to a zinc chloride solution and standing for 2 hours, filtering, drying, keeping warm in a tubular furnace at a temperature of 450° C. for 15 minutes, cooling to room temperature, washing with 1.3 mol / L hydrochloric acid to neutralize, drying, and crushing to obtain activated attapulgite;

[0066] S4. Add 30 kg of deionized water to the activated attapulgite and stir evenly. Pour the prefabricated carboxymethyl cellulose into the mixture while stirring. Stir at a speed of 700 r / min for 18 min. Add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine and stir at a speed of 700 r / min for 2.5 h.

[0067] A method for preparing a vertical anti-seepage material based on modified attapulgite is provided. Alkali-activated blast furnace slag is added to the modified attapulgite slurry obtained in this embodiment and stirred evenly, and the dry mass of the modified attapulgite slurry accounts for 33% of the dry mass of the system.

[0068] Example 5

[0069] A modified attapulgite slurry for vertical anti-seepage materials in contaminated sites, the raw materials of which include: 20 kg of attapulgite, 3 kg of microcrystalline cellulose, 0.5 kg of ammonium ferrous sulfate hexahydrate, 100 kg of 0.5 mol / L zinc chloride solution, 1.8 kg of carboxymethyl cellulose, 2 kg of hexadecyltrimethylammonium bromide, and 2 kg of amino-terminated polyamidoamine.

[0070] The above-mentioned modified attapulgite slurry preparation method comprises the following steps:

[0071] S1, adding carboxymethyl cellulose to 20 kg of anhydrous ethanol and stirring evenly, adding deionized water thereto until the concentration of the carboxymethyl cellulose is 8 mmol / L, to obtain prefabricated carboxymethyl cellulose;

[0072] S2, grinding the attapulgite through a 200 mesh sieve, calcining at high temperature for 2 hours, the calcination temperature is 350° C., and then adding microcrystalline cellulose to grind evenly after cooling, the grinding pressure is 1.6 MPa, and the grinding speed is 3000 r / min to obtain a cellulose-attapulgite composite;

[0073] S3, adding the cellulose-attapulgite composite to 30 kg of water, adding ammonium ferrous sulfate hexahydrate and stirring evenly, hydrothermally treating at a temperature of 220° C. for 8 hours, adding to a zinc chloride solution and standing for 5 hours, filtering, drying, keeping warm in a tubular furnace at a temperature of 400° C. for 20 minutes, cooling to room temperature, washing with 1.2 mol / L hydrochloric acid to neutralize, drying, and crushing to obtain activated attapulgite;

[0074] S4. Add 40 kg of deionized water to the activated attapulgite and stir evenly. Pour the prefabricated carboxymethyl cellulose into the mixture while stirring. Stir at a speed of 600 r / min for 20 min. Add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine and stir at a speed of 600 r / min for 3 h.

[0075] A method for preparing a vertical anti-seepage material based on modified attapulgite is provided. 42.5-grade ordinary Portland cement is added to the modified attapulgite slurry obtained in this embodiment and stirred evenly, and the dry mass of the modified attapulgite slurry accounts for 30% of the dry mass of the system.

[0076] Comparative Example 1

[0077] A modified attapulgite slurry for vertical anti-seepage materials in polluted sites, the raw materials of which include: 20kg of attapulgite, 3kg of microcrystalline cellulose, 1.8kg of carboxymethyl cellulose, 2kg of hexadecyltrimethylammonium bromide, and 2kg of amino-terminated polyamidoamine.

[0078] The above-mentioned modified attapulgite slurry preparation method comprises the following steps:

[0079] S1, adding carboxymethyl cellulose to 20 kg of anhydrous ethanol and stirring evenly, adding deionized water thereto until the concentration of the carboxymethyl cellulose is 8 mmol / L, to obtain prefabricated carboxymethyl cellulose;

[0080] S2, grinding the attapulgite through a 200 mesh sieve, calcining at high temperature for 2 hours, the calcination temperature is 350° C., and then adding microcrystalline cellulose to grind evenly after cooling, the grinding pressure is 1.6 MPa, and the grinding speed is 3000 r / min to obtain a cellulose-attapulgite composite;

[0081] S3. Add 40 kg of deionized water to the cellulose-attapulgite composite and stir evenly. Pour the prefabricated carboxymethyl cellulose into the composite under stirring, stir at a speed of 600 r / min for 20 min, add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine, and stir at a speed of 600 r / min for 3 h.

[0082] A method for preparing a vertical anti-seepage material based on modified attapulgite comprises adding 42.5-grade ordinary Portland cement to the modified attapulgite slurry obtained in this comparative example and stirring the mixture uniformly, wherein the dry mass of the modified attapulgite slurry accounts for 30% of the dry mass of the system.

[0083] Comparative Example 2

[0084] A modified attapulgite slurry for vertical anti-seepage materials in contaminated sites, the raw materials of which include: 20 kg of attapulgite, 3 kg of microcrystalline cellulose, 0.5 kg of ammonium ferrous sulfate hexahydrate, 100 kg of 0.5 mol / L zinc chloride solution, 1.8 kg of carboxymethyl cellulose, and 2 kg of hexadecyltrimethylammonium bromide.

[0085] The above-mentioned modified attapulgite slurry preparation method comprises the following steps:

[0086] S1, adding carboxymethyl cellulose to 20 kg of anhydrous ethanol and stirring evenly, adding deionized water thereto until the concentration of the carboxymethyl cellulose is 8 mmol / L, to obtain prefabricated carboxymethyl cellulose;

[0087] S2, grinding the attapulgite through a 200 mesh sieve, calcining at high temperature for 2 hours, the calcination temperature is 350° C., and then adding microcrystalline cellulose to grind evenly after cooling, the grinding pressure is 1.6 MPa, and the grinding speed is 3000 r / min to obtain a cellulose-attapulgite composite;

[0088] S3, adding the cellulose-attapulgite composite to 30 kg of water, adding ammonium ferrous sulfate hexahydrate and stirring evenly, hydrothermally treating at a temperature of 220° C. for 8 hours, adding to a zinc chloride solution and standing for 5 hours, filtering, drying, keeping warm in a tubular furnace at a temperature of 400° C. for 20 minutes, cooling to room temperature, washing with 1.2 mol / L hydrochloric acid to neutralize, drying, and crushing to obtain activated attapulgite;

[0089] S4. Add 40 kg of deionized water to the activated attapulgite and stir evenly. Pour the prefabricated carboxymethyl cellulose into the activated attapulgite under stirring, stir at a speed of 600 r / min for 20 min, add hexadecyltrimethylammonium bromide, and stir at a speed of 600 r / min for 3 h.

[0090] A method for preparing a vertical anti-seepage material based on modified attapulgite comprises adding 42.5-grade ordinary Portland cement to the modified attapulgite slurry obtained in this comparative example and stirring the mixture uniformly, wherein the dry mass of the modified attapulgite slurry accounts for 30% of the dry mass of the system.

[0091] The same mass of the modified attapulgite-based vertical anti-seepage material obtained in Example 5 and Comparative Examples 1-2 was poured into a mold, demolded after solidification, cured for 28 days, and then its unconfined compressive strength and permeability coefficient were measured.

[0092] The results are as follows Figure 1 As shown, the vertical anti-seepage material obtained in Example 5 has better unconfined compressive strength and lower permeability coefficient, indicating that the vertical anti-seepage material obtained in the present invention can effectively enhance the crack resistance of the system and greatly enhance the bearing capacity of the vertical anti-seepage material. At the same time, hexadecyltrimethylammonium bromide is used as a cationic surfactant and compounded with activated attapulgite and amino-terminated polyamide amine to make the product have excellent adsorption performance, which can further enhance the blocking effect of pollutants in the leachate of the contaminated site after the wall is formed.

[0093] The adsorption retardation rate of each group of samples for different pollutants (chemical oxygen demand, ammonium nitrogen, phosphate, sulfate ion, and heavy metal ion Pb) was further tested.

[0094] like Figure 2 As shown, the adsorption and retardation rate of the vertical anti-seepage material obtained in Example 5 for pollutants is better than that in the comparative example. It is confirmed that the present invention can greatly improve the adsorption and retardation capacity of pollutants and enhance the resistance to sulfate corrosion by modifying the attapulgite and rationally matching and compounding with materials such as hexadecyltrimethylammonium bromide and amino-terminated polyamide amine to form a cross-overlapping effect, and can effectively prevent the intrusion of pollutants such as sulfate anions in solid waste dumps, thereby achieving the purpose of long-term vertical anti-seepage and barrier of polluted sites.

[0095] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A modified attapulgite slurry for vertical anti-seepage material of polluted sites, characterized in that: The raw materials include: attapulgite, microcrystalline cellulose, a catalyst, a zinc chloride solution with a concentration of 0.1-1 mol / L, carboxymethyl cellulose, hexadecyltrimethylammonium bromide and amino-terminated polyamide amine; the mass ratio of attapulgite, microcrystalline cellulose, a catalyst, zinc chloride solution, carboxymethyl cellulose, hexadecyltrimethylammonium bromide and amino-terminated polyamide amine is 10-30: 1-5: 0.1-1: 50-150: 1-2.5: 1-3: 1-3.

2. The modified attapulgite slurry for vertical anti-seepage material of contaminated sites according to claim 1, characterized in that: The catalyst is ammonium ferrous sulfate hexahydrate.

3. A method for preparing modified attapulgite slurry for vertical anti-seepage material for contaminated sites as claimed in claim 1 or 2, characterized in that: The steps include: S1, adding carboxymethyl cellulose to anhydrous ethanol and stirring evenly, and adding deionized water thereto to obtain prefabricated carboxymethyl cellulose; S2, grinding and sieving the attapulgite, calcining at high temperature for 1-3 hours, the calcination temperature is 200-500° C., and then adding microcrystalline cellulose after cooling and grinding evenly to obtain a cellulose-attapulgite composite; S3, adding the cellulose-attapulgite complex to water, adding a catalyst and stirring evenly, hydrothermally treating at 200-240° C. for 5-10 hours, taking out and placing in a zinc chloride solution for 1-10 hours, filtering, drying, keeping warm in a tubular furnace at 300-500° C. for 10-30 minutes, cooling to room temperature, washing to neutrality, drying, and crushing to obtain activated attapulgite; S4. Add deionized water to the activated attapulgite and stir evenly, pour prefabricated carboxymethyl cellulose into it under stirring, add hexadecyltrimethylammonium bromide and amino-terminated polyamidoamine and stir.

4. The method for preparing modified attapulgite slurry for vertical anti-seepage material for contaminated sites according to claim 3, characterized in that: In S1, deionized water is added until the concentration of carboxymethyl cellulose in the system is 5-10 mmol / L.

5. The method for preparing modified attapulgite slurry for vertical anti-seepage material for contaminated sites according to claim 3, characterized in that: In S2, the grinding pressure is 1-2.5 MPa, and the grinding speed is 1000-5000 r / min.

6. The method for preparing modified attapulgite slurry for vertical anti-seepage material for contaminated sites according to claim 3, characterized in that: In S3, 1-1.5 mol / L hydrochloric acid is used for washing to neutralize the mixture.

7. A vertical anti-seepage material based on modified attapulgite, characterized in that: The raw materials include: the modified attapulgite slurry used for vertical anti-seepage materials in contaminated sites as claimed in claim 1 or 2 and a consolidating material; the consolidating material is a hydraulic material and / or soil.

8. The vertical anti-seepage material based on modified attapulgite according to claim 7, characterized in that: The dry mass of the modified attapulgite slurry used for vertical anti-seepage material of contaminated sites as claimed in claim 1 or 2 accounts for 25-35% of the dry mass of the system.

9. The vertical anti-seepage material based on modified attapulgite according to claim 7, characterized in that: The hydraulic material is at least one of ordinary Portland cement, slag Portland cement, alkali-activated blast furnace slag, fly ash, alkali slag, and carbide slag.

10. The vertical anti-seepage material based on modified attapulgite according to claim 7, characterized in that: The soil is at least one of waste soil from on-site trench excavation, clay, and silt.

11. A method for preparing a vertical anti-seepage material based on modified attapulgite according to any one of claims 7 to 10, characterized in that: Add consolidation materials into the modified attapulgite slurry used as vertical anti-seepage material for contaminated sites as claimed in claim 1 or 2 and stir evenly.

12. A vertical anti-seepage material based on modified attapulgite as claimed in any one of claims 7 to 10 used as a vertical isolation wall material for a contaminated site.